Trapped in a Vice : The Consequences of Confinement for Young People - Cox, Alexandra L., 1978- (Book collections on Project MUSE., 2017)
Trapped in a Vice explores the consequences of a juvenile justice system that is aimed at promoting change in the lives of young people, yet ultimately relies upon tools and strategies that enmesh them in a system that they struggle to move beyond. The system, rather than the crimes themselves, is the vice. Trapped in a Vice explores the lives of the young people and adults in the criminal justice system, revealing the ways that they struggle to manage the expectations of that system; these stories from the ground level of the justice system demonstrate the complex exchange of policy and practice.